The simplest form is probably this one:

"If the remaining trinomial is still of the form ax2 + bx + c, find two integers, r and s, whose sum is b and whose product is ac. Then rewrite the trinomial as ax2 + rx + sx + c and use grouping and the distributive property to factor the polynomial."

I.e. 6x^2 - 8x -30 has ac=-180 and b=-8. So r=10 and s=-18 works.

Now you get 6x^2 + 10x - 18x - 30 which is (3x+5)(2x-6).

(Note that we could have first divided everything by 2 to make the numbers smaller.)